حماية حقوق الإنسان فى ظل منظمة الأمم المتحدة - واصل، سامى جاد عبدالرحمن (الجمعية المصرية للاقتصاد السياسي والإحصاء والتشريع, 2016)
The UN Charter provided human rights and fundamental freedoms as one of the purposes of the United Nations, and pointed out these rights in more than one place, then the Universal Declaration of Human Rights ensured these rights. UN adopted a number of international conventions in the field of protection and development of human rights, which formed what is known as the UN system of human rights, to be performed through several mechanisms, such as Commission on Human Rights, UNHCHR, and Human Rights Council. UN adopted the idea of “humanitarian intervention” to suppress serious violations of human rights, then replaced it with the idea of “responsibility to protect”, but they have failed to put an end to many of these violations. Some recommendations have been proposed to promote the human rights protection system.
أولى ميثاق الأمم المتحدة حقوق الإنسان وحرياته الأساسية عنايته، ونص عليها باعتبارها أحد مقاصد الأمم المتحدة، وأشار إلى هذه الحقوق في أكثر من موضع، ثم استكمل الإعلان العالمي لحقوق الإنسان ما بدأه الميثاق. تبنت الأمم المتحدة عدد غير قليل من المواثيق والصكوك الدولية في مجال حماية وتطوير حقوق الإنسان شكلت ما يعرف بمنظومة الأمم المتحدة لحقوق الإنسان، التي يتم تنفيذها من خلال عدة آليات، من أهمها لجنة حقوق الإنسان، والمفوضية السامية لحقوق الإنسان، ومجلس حقوق الإنسان. اعتمدت الأمم المتحدة فكرة "التدخل الإنساني" لقمع الانتهاكات الخطيرة لحقوق الإنسان، ثم ما لبثت أن استبدلتها بفكرة "مسئولية الحماية"، بيد أنها أخفقت في وضع حد للعديد من هذه الانتهاكات. وأخيراً، تم اقتراح بعض التوصيات التي من شأنها تطوير آليات حماية حقوق الإنسان.
Keywords: حقوق الإنسان -- لجنة حقوق الإنسان -- مجلس حقوق الإنسان -- منظمة الأمم المتحدة